Model results for the ionospheric lower transition height over mid-latitude - J. Lei; J. Lei; L. Liu; W. Wan; S.-R. Zhang (Annales Geophysicae, 2004)
Theoretical calculations of the ionospheric lower transition height (LTH), a level of equal O+ and molecular ion densities, were performed and compared with empirical models by Zhang et al. (1996). This paper represents a substantial extension of the prior work by including the AE-C data of ion composition analysis and by detailed quantitative studies of the LTH simulation, and by creating a new LTH empirical model based on our simulations. Results show that: (1) the calculated LTH, in general, is lowest near 11-13LT and reaches the diurnal maximum after midnight (about 01~02LT). The local time asymmetry becomes more evident in summer, when the time of minimum shifts to 16LT. (2) The simulated LTH presents a dominant, semiannual variation during nighttime, and a pronounced annual variation during daytime. (3) The simulated LTH increases with solar activity at night and decreases by day, while the standard IRI option has an opposite tendency at night in summer and equinox. Therefore, the day-night difference of simulated LTH significantly increases with solar activity. (4) Both daytime and nighttime LTHs, tend to increase with the increasing geomagnetic activity Ap index, with a mean slope about 0.1455km per Ap unit. (5) The diurnal variation of LTH is found to be more than 20 km, which is much larger than the seasonal variation under F107=100 and Ap=10. Thus, the diurnal and solar activity variations of LTH are more pronounced than its seasonal and magnetic activity variations.